Room-temperature synthesized SnO2 electron transport layers for efficient perovskite solar cells. Issue 18 (29th March 2019) - Shi, Shengwei; Li, Jing; Bu, Tongle; Yang, Shili; Xiao, Junyan; Peng, Yong; Li, Wei; Zhong, Jie; Ku, Zhiliang; Cheng, Yi-Bing; Huang, Fuzhi
Abstract : Room-temperature processed SnO2 as electron transport layer materials for efficient flexible perovskite solar cells. Abstract : Tin oxide (SnO2 ) is widely used as electron transport layer (ETL) material in perovskite solar cells (PSCs). Numerous synthesis methods for SnO2 have been reported, but they all require a proper thermal treatment for the SnO2 ETLs. Herein we present a simple method to synthesize SnO2 nanoparticles (NPs) at room temperature. By using butyl acetate as a precipitator and a proper UV–Ozone treatment to remove Cl residuals, excellent SnO2 ETLs were obtained without any thermal annealing. The highest power conversion efficiency (PCE) of the prepared PSCs was 19.22% for reverse scan (RS) and 18.79% for forward scan (FS). Furthermore, flexible PSCs were fabricated with high PCEs of 15.27%/14.74% (RS/FS). The low energy consuming SnO2 ETLs therefore show great promise for the flexible PSCs' commercialization.